2004
DOI: 10.1002/ijc.20732
|View full text |Cite
|
Sign up to set email alerts
|

Proximity of first intercourse to menarche and the risk of human papillomavirus infection: A longitudinal study

Abstract: Cross-sectional studies have suggested that compared with women who delay the start of their sexual career, those who first have intercourse soon after menarche are more susceptible to cervical human papillomavirus (HPV) infection and thus have a greater risk of cervical neoplasia. We describe, using longitudinal observations, how the risk of infection with HPV varies with the interval between menarche and first intercourse in 474 women aged 15-19 recruited within 12 months of first intercourse and before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 8 publications
7
37
0
2
Order By: Relevance
“…Although a previous report (23) suggested an inverse association between age at menarche and HPV infection, our findings are in agreement with the majority of the studies that did not report significant associations (10,17,24).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although a previous report (23) suggested an inverse association between age at menarche and HPV infection, our findings are in agreement with the majority of the studies that did not report significant associations (10,17,24).…”
Section: Discussionsupporting
confidence: 93%
“…Studies on the influence of OC use on HPV infection showed inconsistent results, with modest associations in both directions (10,12,13,(18)(19)(20)(21)(22). Very little is known on the relationship of age at menarche (10,17,23,24) or menopause (25) with HPV infection or cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although this possibility cannot be ruled out, it is unlikely to involve a specific vulnerability of the cervix to HPV infections in the interval shortly after menarche because we observed a steady increase in ICC risk with decreasing age at first intercourse across the age range considered and not exclusively in the ages surrounding menarche. This conclusion is also supported by a prospective study of HPV infection risk in the first years after menarche (70).…”
Section: Discussionsupporting
confidence: 55%
“…Biologically, we found that early sexual activity after menarche (< 6 years) led to greater susceptibility to SCCA. During puberty, the immaturity of cervical cells undergo many changes that might be more vulnerable to damage and HPV infection and/or other sexually-transmitted diseases (Coker et al, 1994;Kahn et al, 2002;Collins et al, 2005;Matos et al, 2005;Louie et al, 2009). This data indicates that a delay of 6 or more years after menarche before sexual intercourse would be safer and afford some protection from sexually-transmitted diseases (including HPV infection) and susceptibility to cervical cancer.…”
Section: Discussionmentioning
confidence: 99%